Yoga And Mental Health: A Review On Efficacy Of Yoga In Managing Stress, Anxiety And Depression - Kothari, Anil (International Research Journal of Ayurveda & Yoga, 2021)
Yoga is a holistic multidimensional system of health that was used by ancient sages to achieve states of transcendence and develop special mental abilities and wellbeing. Essentially a yoga therapy is a type of alternative therapy that uses Asanas (Physical postures), Pranayamas (Breathing techniques), Dhyana (Meditation), Shatkarma (Internal cleansing), Mudras (Hand postures) and Bandhas (Locks) to reduce the impact of exaggerated stress responses which in turn decreases physiological arousal and may be helpful for both anxiety and depression. This review presents a summary of scientific evidences from randomized controlled trials, review articles and Hatha yoga texts on the effects of yoga in promoting mental health by alleviating the symptoms of mental disorders.